Overexpression of BNIP3 in renal carcinoma cells can promote apoptosis of renal carcinoma cells through HIF-1α-BNIP3-mediated autophagy - Huang, Long; Wang, Lin; Yuan, Dan; Xu, Yan; Wang, Yu; Yao, Kai; Zhong, Xiao; Liu, Quanda; Jia, Kang; Lei, Lei; Wang, Haiyan; Liu, Dongliang (Frontiers in Oncology, 2025)
BackgroundRenal cell carcinoma (RCC) is a prevalent malignancy with limited effective therapies, necessitating novel molecular targets. BNIP3, a pro-apoptotic protein regulated by hypoxia-inducible factor 1 (HIF-1), is implicated in autophagy and apoptosis, but its role in RCC under hypoxic conditions remains underexplored. This study investigates the effects of BNIP3 overexpression on RCC cell behavior and its molecular mechanisms.MethodsHuman RCC cell lines A498 and 786-O were transfected with pcDNA3.1-BNIP3 to overexpress BNIP3 and cultured under normoxic (21% O2) or hypoxic (1% O2) conditions. Proliferation, invasion, and apoptosis were assessed using CCK-8, cell cloning, Transwell, and flow cytometry assays. Autophagy was evaluated via immunofluorescence, transmission electron microscopy, and Western blot analysis of LC3B and p62. Co-immunoprecipitation examined Bcl-2/Beclin1 interactions. In vivo tumor growth was studied using BALB/c nude mice with 786-O xenografts.ResultsBNIP3 overexpression significantly reduced proliferation and invasion while increasing apoptosis in A498 and 786-O cells (P<0.01). Under hypoxia, BNIP3 disrupted the Bcl-2/Beclin1 complex, enhancing autophagy by increasing LC3B and autophagosome formation and decreasing p62 (P<0.01). Autophagy inhibitor 3-MA suppressed BNIP3-induced apoptosis, indicating autophagy-dependent apoptosis. In vivo, BNIP3 overexpression decreased tumor volume, Ki67 expression, and increased apoptosis and autophagy markers (P<0.01).ConclusionBNIP3 overexpression inhibits RCC progression by promoting HIF-1α-mediated autophagy and subsequent apoptosis under hypoxic conditions, primarily through disrupting the Bcl-2/Beclin1 complex. These findings establish BNIP3 as a potential therapeutic target for RCC, warranting further investigation into autophagy-based interventions.